The Impact Of Smartphone Technology On Behavior Of Parents For Aged 40-50 Years: (Case Study: Desa Rawang Baru, Rawang Panca Arga-Asahan Destrict) - Hasanuddin Sirait (LLDIKTI Wilayah 1 Sumatera Utara, 2022)
Good parents' behavior indicates the existence of a personality life from a daily mindset that always leads to positive things, positive behavior from parents can have a very big impact on the survival of family life and social life.In modern times there are many deviations in behavior carried out by people.This times allegedly caused by advances in communication technology, one of which is smartphone technology. It is less able to use the applications contained in Smartphone today such as fb, browsing, listening to music, video players, games, allegedly very influential on the behavior of parents today. That is why the writer feels important to conduct research with the title